Improvement of residents’ happiness index in tourism destinations based on guiding significance and tourism development - Lisha, Liu; Abdullah, Nawal Hanim; Ramachandran, Sridar; Raja Yusof, Raja Nerina (Informa UK Limited, 2023)
Tourism has been widely recognized as a powerful tool for economic growth in rural communities around the world. The growth of rural tourism has always been a significant start in targeting poverty alleviation and promoting economic change in rural China. Rural tourism development is the participation of rural people in tourism and full integration into tourism development. Rural tourism development depends on the participation and support of rural residents. Therefore, this research explores the influencing factors of rural tourism residents’ happiness and their influence on tourism support. The sample was selected from Anren Town, Chengdu City, China, and the research subjects were residents of Anren Town. In this study, data were collected from 370 residents of Anren Town via a questionnaire survey. The results show that Community Involvement (CI) and Community Attachment (CA) positively affect residents’ Authentic Happiness (AH). This research found that improving residents’ support for tourism development can promote the development of rural tourism. The study finding provides a new perspective for the treatment of residents’ problems in tourism development and has guiding significance for the improvement of residents’ happiness index in tourism destinations. If the community is better, the happiness of the residents will be stronger.